Financial development, crises, and recovery in small open economies - Raza, Hamid (University of Limerick, 2016)
peer-reviewed This study contributes to the existing literature on nancial development, crises, and recovery in small open economies. In this dissertation, we use Iceland as an example of a small open economy with a sovereign currency and compare it with Ireland and other periphery countries from the EMU. We critically examine the developments that preceded the crises in Iceland and Ireland with an emphasis on the role of capital in ows. We then empirically investigate the recovery pattern in Iceland and other peripheral countries. Our ndings can be summarised as follows. The process of nancial development and its interaction with the real sector in Iceland and Ireland greatly di er primarily due to their exchange rate regimes amongst other things. Comparing the two countries, we nd that the adjustment following a sudden stop to a capital in ow was faster in Iceland but the collapse more serious. In particular, the current account adjustment was the result of real exchange rate depreciations and domestic demand compression. For Ireland and other members of the euro zone, the adjustment process is much slower. The adjustment in the current account has been the result of domestic demand compression in these countries, which have resulted in long-lasting recessions, de ation and high unemployment in Ireland, as well as in Italy, Portugal and Spain. Moreover, our ndings suggest that the role of capital controls combined with nancial restructuring was crucial in the post{crisis period in Iceland. Finally, we present a macroeconomic framework in order to understand the process of crisis and recovery in small open economies. We demonstrate the generation of nancial crisis and the subsequent adjustment process in a sovereign currency regime through the use of simulations.